THE SKIRMISH AT GRASSPLATZ (26 SEPTEMBER, 1914) - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
In 1969, Harry Klein’s unit history, known as Light Horse Cavalcade. The Imperial Light Horse 1899-1961, appeared in Cape Town. Established in September 1899, this unit, now renamed the Light Horse Regiment, participated actively in the Anglo Boer War, 1899-1902, and in World War 2,1939-1945.